"Stormy Weather" by Galaktion Tabidze and "William Tell" by Friedrich Schiller - Sikharulidze, Natia (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2016)
A poem by Galaktion Tabidze, Stormy Weather, is analysed in this article. The poem was inspired by one passage from William Tell, the drama by Friedrich Schiller. Understanding the main message of William Tell as a primary source helps us to analyse and appreciate the deeper layers of the Georgian poet’s work. With reference to Schiller’s work, Stormy Weather can be interpreted as an allegory. It also becomes obvious that Galaktion Tabidze points to tyranny and cruelty of people and divine retribution from Mother Nature. It can be said that Stormy Weather is the poet’s evaluation of the 30s of the 20th Century.